A study of the fire smoke propagation in subway station under the effect of piston wind - Zhong, Wei; Tu, Rui; Yang, Jian Peng; Liang, Tian Shui (Journal of Civil Engineering and Management, 2015)
A running traffic train induces piston wind in the subway. The influence of piston wind on fire smoke propagation in subway is investigated numerically. The flow field structure in fire platform, temperature contours and velocity profiles at certain positions are obtained at various scenarios respectively. Three methods are adopted to reduce the impact of piston wind on smoke layers. Results show that large-scale vortexes and tremendous horizontal inertial force would be produced under the influence of piston wind; and that smoke stratification would be broken totally under its influence, therefore toxic gas would spread to subway hall through stairs. So the former smoke management system in a subway station becomes less effective. Results also show that combination of enhanced the volume flux of pressurization at the subway hall and lowering the height of smoke screens around stairs are necessary to restrict hazard smoke on the floor on fire. The bypass wind tunnel and ventilation shaft are useful to attenuate the magnitude of piston wind.